2015
DOI: 10.1021/acs.biochem.5b00746
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Full Catalytic Cycle among Multiple Cyclophilin Family Members and Limitations on the Application of CPMG-RD in Reversible Catalytic Systems

Abstract: Cyclophilins catalyze cis ↔ trans isomerization of peptidyl–prolyl bonds, influencing protein folding along with a breadth of other biological functions such as signal transduction. Here, we have determined the microscopic rate constants defining the full enzymatic cycle for three human cyclophilins and a more distantly related thermophilic bacterial cyclophilin when catalyzing interconversion of a biologically representative peptide substrate. The cyclophilins studied here exhibit variability in on-enzyme int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 44 publications
3
12
0
Order By: Relevance
“…This variability indicates that, while altering conformational sampling does influence enzymatic function in CypA toward multiple substrates, the specific outcomes are somewhat substrate specific, likely due to differences in the substrate/active-site interactions within each enzyme/substrate complex. While previous correlative measures have hinted at a role for micro- to millisecond dynamics in the catalytic cycle of CypA (Eisenmesser et al, 2005; Fraser et al, 2009; Holliday et al, 2015a), here we have shown a direct connection between the dynamic networks of CypA identified via our RASSMM approach and catalysis of multiple substrates.…”
Section: Resultssupporting
confidence: 41%
See 3 more Smart Citations
“…This variability indicates that, while altering conformational sampling does influence enzymatic function in CypA toward multiple substrates, the specific outcomes are somewhat substrate specific, likely due to differences in the substrate/active-site interactions within each enzyme/substrate complex. While previous correlative measures have hinted at a role for micro- to millisecond dynamics in the catalytic cycle of CypA (Eisenmesser et al, 2005; Fraser et al, 2009; Holliday et al, 2015a), here we have shown a direct connection between the dynamic networks of CypA identified via our RASSMM approach and catalysis of multiple substrates.…”
Section: Resultssupporting
confidence: 41%
“…Specifically, R 2 -RD experiments have revealed that nearly 50% of residues within CypA exhibit micro- to millisecond timescale dynamics and that they comprise rates of motion spanning nearly an order of magnitude. More recently, the segmental nature of dynamics in CypA has also been independently confirmed by variable-temperature X-ray crystallography (Keedy et al, 2015) and we have shown that distinct segmental dynamics persist in solution in the presence of saturating concentrations of substrate (Holliday et al, 2015a). Collectively, these studies reveal that significant global communication occurs between non-coherent regions such that mutagenesis or substrate binding affects motions across the protein at sites reporting on distinct structural transitions.…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…In NMR studies of CypA, a dynamic continuum has been identified such that the relaxation profiles cannot be globally fit to one or two exchange phenomena and are instead indicative of more localized motions (22). Exchange rates coalesce somewhat during turnover, perhaps suggesting an increase in coordination throughout the protein, but appear to still consist of localized motions that are not fully coherent (23). However, dynamical signals during catalytic turnover could be affected by substrate binding and unbinding, especially if the substrate binding affinity is low, thereby leading to ambiguity in the interpretation of NMR analysis (23).…”
mentioning
confidence: 99%